Screening and characterization of highly responsive genes related to the blast disease caused by Pyricularia oryzae in rice (Oryza sativa) - Huy Gioi, Dong; Duc Ha, Chu; Quoc Trung, Nguyen; Van Thang, Bui; Van Tien, Tran; Thi Thu Huong, Bui (Journal of Forestry Science and Technology, 2023)
Blast, caused by Pyricularia oryzae, has been regarded as one of the most critical diseases in rice plants (Oryza sativa). Seeking a list of candidate genes is a major step for resistance breeding programs. In this study, at least 24 RNA-Seq datasets related to blast disease infection in rice plants have been obtained from databases. Among them, four microarray datasets obtained from blast-infected leaf samples in Indica rice varieties, including GSE122258, GSE126961, GSE78266 and GSE39635 were selected for further in silico analysis. Particularly, a total of 216 differentially expressed genes in blast-treated leaves were obtained by exploring four microarray atlas. Among them, at least 32 blast-responsive genes that exhibited similar expression patterns were selected for further bioinformatics analysis. Particularly, these differentially expressed genes encode important transcription factors and enzyme families. By using Expasy and Yloc tools, the physic-chemical properties of these proteins, including lengths, molecular weights, iso-electric points and grand average of hydropathy were greatly variable and the majority of these blast-responsive gene-encoding proteins was localized in the cytoplasm and nucleus. To sum up, this current study has provided fundamental knowledge about potential candidate differentially expressed genes for further functional characterization of genes aiming to control blast resistance in rice